Theoretical Basis Of The Company Competitiveness Assessment - Belkin, Vladimir Nikiforovich; Belkina, Nadezhda Andreyevna; Vladykina, Larisa Borisovna (Economy of Regions, 2015)
The article deals with the basic theoretical questions of the company competitiveness assessment. The state of modern economic thought on this issue is shown. The main factors of the company competitiveness are specified. A specific role of staff of an enterprise is revealed: on the one hand, it is a resource, on the other is a subject, resulting in productive movement all factors of competitiveness, i.e. the staff is a critical factor in the company competitiveness. The criterion of company competitiveness is proposed, on its basis, the concept of “competitive enterprise” is defined. The most well-known approaches for assessing the company competitiveness are analyzed. The author's method of the company competitiveness assessment based on the dynamics of the integral index of competitiveness is provided. For those cases, when it is impossible to determine the proportion of products on the market, it is proposed to evaluate the company competitiveness on the profitability of its production. The article shows the experience in calculating of the company competitiveness on the proposed author's methods.